FORMATION OF CREATIVE COMMUNICATION SKILLS OF PRIMARY SCHOOL STUDENTS (Scientific journal of the Fergana State University, 2023)
The article is one of today's current topics and is aimed at forming the communication skills of elementary school students. The importance of the use of communication in the development of independent and creative thinking of elementary school students, the problems of finding content of other psychological characteristics and volitional qualities, and their effects on the formation of communication are discussed. Also, issues of raising a spiritually mature generation through education based on a person-oriented, competency-based approach were discussed.